The economic burden and quality of life of patients with psoriasis treated with biologics in China - Shuhui Min; Danfeng Wang; Jiali Xia; Xiao Lin; Guan Jiang (Taylor & Francis Group, 2023)
Background Although biologics improve the quality of life of psoriasis patients, they also impose a substantial economic burden. There is a lack of research addressing the economic and humanistic impact of biologics in China. Objective This cross-sectional investigation aims to assess the economic cost, quality of life, and patient satisfaction among individuals with psoriasis treated with biologics and non-biologics. Methods From July 2021 to December 2022, eligible patients with psoriasis were recruited through both on-site and online questionnaire completion. The questionnaires collected sociodemographic data, clinical characteristics of psoriasis, economic costs associated with treatment, and the Dermatological Life Quality Index (DLQI). Results 481 patients with a mean age of 40.8 ± 13.4 years old were included and classified into a non-biologic (n = 195) and biologic (n = 286) treatment group. The direct medical cost for non-biologics patients was 7,249 CNY, accounting for 70.0% of the total cost, while biologics patients incurred 15,176 CNY, making up 94.3% of the total cost. The non-biologic group had higher costs related to hospitalization, self-purchase of drugs, and indirect costs than the biologic treatment group. Additionally, DLQI scores were higher in the non-biologic group. Conclusion Patients in the biologic group experienced a higher economic burden and better quality of life than those in the non-biologic group.